A review of the genera Prismognathus Motschulsky and Cladophyllus Houlbert (Coleoptera: Scarabaeoidea: Lucanidae) from China, with the description of two new species - Huang, Hao; Chen, Chang-Chin (Zootaxa, 2012)
A classification scheme is provided for the genera Cladophyllus Houlbert, Cyclorasis Thomson, Eligmodontus Houlbert,Gonometopus Houlbert, Prismognathus Motschulsky and Tetrarthrius Didier. The Chinese species of Prismognathus (in thepresent sense) and Cladophyllus are reviewed, with the male and female genitalia illustrated. New distribution data are givenfor some Chinese species. Two new species of Prismognathus are described, P. haojiani new species from Guizhou, and P. shani new species from Sichuan. Keys to males and females of the Chinese Prismognathus and Cladophyllus are also given.